Keterbukaan Kodrati Manusia Kepada Yang Ilahi Dalam L’action 1893 Maurice Blondel - Hayon, Bernard (Jurnal Orientasi Baru, 2009)
Maurice Blondel, born in Dijon, Paris, November 2, 1891, was one among thegreatest philosophers of the twenty century. In his ‘philosophy of action’ hewas developing classic Neo-Platonism and modern Pragmatism in one contextof Christian philosophy. His most concern was to overcome the old splitbetween faith and reason. In his l’Action (1893) he bridged the gap betweentheory and praxis, which was once created by Kant. Action is the key term inhis philosophy, for it is precisely the very bridge that unites between the two.Action is vinculum subtantiale (substansial chain) which bind ideas or thought,which is in mind and facts, which exists outside. Yet he convinced also that‘action’ itself never satisfies the quench of man. The need of man is unlimitedand would only be met by the perfecting ‘action’ which is God Himself.